The invention of Malaysian traditional game into mobile game apps: a case study of Tarik Upih / Ilinadia Jamil and Zainal Kadir - Jamil, Ilinadia; Kadir, Zainal (2015)
Malaysian traditional game was a popular culture once. Unfortunately, these precious tradition are fading from the memory of Malaysian society especially young generation. Furthermore, the preference of today's teenagers towards mobile game endangered the existence of traditional game. This research provides an attempt to commercialized and promote the value of traditional game which can be preserved and suit today's trend. Several methods such as observation and reference were used in the study. Although the research is not very extensive, the findings suggest that the traditional games are possible to be innovate into the screen based application. The objective of this research is to identify the most suitable content in design and gameplay that can be developed into mobile game and to measure the effectiveness of mobile game in preserving our culture that suit today’s generation. Nevertheless, this is the preliminary conceptual game based on Tarik Upih, which will open a new dimension of commercializing the traditional games. In a nutshell, the Tarik Upih game would be another new approach that is capable to be introduced to the society.